Sensitivity Analysis of the Estimation of the Single-Number Sound Absorption Evaluation Index $DL_α$ - BATKO, Wojciech; PAWLIK, Paweł; WSZOŁEK, Grażyna (Archives of Acoustics, 2017)
Acoustic barriers are assigned to the respective categories of sound absorbing properties on the basis of a single-number sound absorption evaluation index. Categories of absorbing properties play a significant role in selecting the barrier type for the given localisation. The estimation of the single-number sound absorption evaluation index is performed, among others, by means of measuring the sound absorption coefficient of the analysed acoustic barrier sample in the reverberation chamber.The sensitivity analysis of the determination of the single-number sound absorption evaluation index was performed in this work. The estimation of the input parameters uncertainty contribution to the expanded uncertainty of the sound absorption evaluation index, was done first. The Monte Carlo method and the reduction interval arithmetic were used for this aim.The relative sensitivity coefficients were determined by means of the author’s method based on the interval arithmetic. These coefficients contain information concerning the quantitative influence of the given input value on the final result.